Does sarcopenia originate in early life? findings from the Hertfordshire cohort study - Sayer, A; Syddall, H; Gilbody, H; Dennison, E; Cooper, C (2004)
Background. Sarcopenia is defined as the loss of skeletal muscle mass and strength with aging. Recent epidemiological studies have shown that men and women who grew less well in early life have lower muscle strength. Our objective was to investigate the relationship between birth weight, infant growth, and the development of sarcopenia. Methods. We studied 730 men and 673 women, of known birth weight and weight at 1 year, who were born in Hertfordshire, U.K., between 1931 and 1939. Participants completed a health questionnaire, and we measured their height, weight, and grip strength. Standard deviation scores for birth weight, and for infant growth conditional on birth weight, were analyzed in relation to grip strength before and after adjustment for adult size. Results. Grip strength was most strongly associated with birth weight in men (r = 0.19, p < .001) and women (r = 0.16, p < .001). These relationships remained significant after adjustment for adult height and weight. In contrast, the associations with infant growth were weakened after allowing for adult size. Adjustment for age, current social class, physical activity, smoking, and alcohol did not affect these results. Conclusions. Birth weight is associated with sarcopenia in men and women, independently of adult height and weight. The influence of infant growth on long-term muscle strength appears to be mediated through adult size. Sarcopenia may have its origins in early life, and identifying influences operating across the whole life course may yield considerable advances in developing effective interventions.